2019
DOI: 10.3389/fpsyg.2019.01310
|View full text |Cite
|
Sign up to set email alerts
|

I Hear You, but Do I Understand? The Relationship of a Shared Professional Language With Quality of Care and Job Satisfaction

Abstract: In various industries, individuals from different professions have to work together in a team to achieve their collective goal. Having gone through different educations, team members speak different professional languages, which poses a challenge to communication, and coordination in interprofessional teams. A shared language is believed to improve collaboration. In this study, we examine if a shared language in interprofessional healthcare teams is associated with better relational coordination and if both ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…By continuously explicating and discussing the course content and course vision, she created a shared goal and language, which earlier studies in healthcare have flagged as a prerequisite for effective teamwork. 43 Indeed, the team members explicitly emphasized the importance of her didactical knowledge to the team process. The fact that the leader was passionate about educating the young generation of physicians and was pursuing a master in health professions education may explain this zest for explicating didactics and her student-centered focus.…”
Section: Discussionmentioning
confidence: 99%
“…By continuously explicating and discussing the course content and course vision, she created a shared goal and language, which earlier studies in healthcare have flagged as a prerequisite for effective teamwork. 43 Indeed, the team members explicitly emphasized the importance of her didactical knowledge to the team process. The fact that the leader was passionate about educating the young generation of physicians and was pursuing a master in health professions education may explain this zest for explicating didactics and her student-centered focus.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have explored the connection between relational coordination and psychological safety, a factor that is widely acknowledged as a precondition for learning and change (Edmondson, 2004). For example, Stühlinger et al (2019) found that relational coordination was associated with job satisfaction through its effect on psychological safety, while Carmeli and Gittell (2009) found that relational coordination was associated with learning from failure through its impact on psychological safety. Looking in the opposite direction, psychological safety in obstetric units was positively associated with the communication dimensions of relational coordination through its impact on the relational dimensions of relational coordination (Henrichs, 2013).…”
Section: Learning and Innovationmentioning
confidence: 99%
“…In addition to cross-cutting structures, this review suggests the importance of microprocesses such as psychological safety for helping stakeholders coordinate across differences (e.g., Carmeli & Gittell, 2009;Henrichs, 2013;Stühlinger et al, 2019). Going forward, other microprocesses that enable relational coordination should be explored as well.…”
Section: Microprocesses That Support Relational Coordinationmentioning
confidence: 99%
“…Patient safety and the well-being of trainees may be challenged when trainees are redeployed into unfamiliar clinical settings. [14][15][16] Rapidly evolving protocols, including those detailing appropriate use of PPE-particularly when there are concomitant shortages of these materials-create a level of uncertainty about possible exposures and subsequent risks to family or patients. 17 The decision to fill staffing gaps under pandemic conditions with trainees had to be carefully considered and balanced against the availability of faculty and advanced practice providers who could play similar roles and were more familiar with the workflow in these clinical settings.…”
Section: Patient Safety and Trainee Well-beingmentioning
confidence: 99%